Recent applications of capillary electromigration methods to separation and analysis of proteins - Štěpánová, Sille; Kašička, Václav (Analytica chimica acta, 2016)
This review article describes the significant recent developments in analysis of proteins by capillary electromigration (CE) methods (zone electrophoresis, isotachophoresis, isoelectric focusing, affinity electrophoresis, electrokinetic chromatography and electrochromatography) during the period 2011-2015. Improvements in sample preparation, preconcentration, suppression of adsorption and control of electroosmotic flow, separations by particular CE methods, and the detection schemes used in the analysis of proteins are discussed. Innovative applications of the above CE methods for quality control of protein biopharmaceuticals, protein determination in complex biomatrices, peptide mapping of proteins, and determination of physicochemical parameters of proteins are presented.
Keywords: Affinity electrophoresis; Capillary electrophoresis; Isotachophoresis; proteiny; Review; Isoelectric focusing; Electrophoresis, Capillary; elektroforéza kapilární; Proteins